Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/icad.12628
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed fire increases the number of ground‐nesting bee nests in tallgrass prairie remnants

Abstract: Prescribed burning is a common management technique in tallgrass prairie remnants, but there have been few empirical studies that directly examine burning impacts on the nesting preferences and habitat of ground‐nesting bees. We used emergence traps in remnant tallgrass prairies in western Minnesota, USA to determine whether ground‐nesting bees prefer to nest in burned or unburned prairies. We estimated the total number of nests made by actively nesting bees in burned and unburned patches by assessing each spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Patches of bare ground can also promote wasps and butterflies (Eilers et al 2013; Szczepko et al 2020). In many cases bare patches have less thatch and thus provide easier nest access for ground-nesting bees and wasps (Brokaw et al 2023) and perhaps easier access to soil nutrients needed by butterflies that exhibit puddling behavior (Ankola et al 2021). A second hypothesized explanation for positive response to bare ground is that less vegetative cover creates more favorable microclimates through increased sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Patches of bare ground can also promote wasps and butterflies (Eilers et al 2013; Szczepko et al 2020). In many cases bare patches have less thatch and thus provide easier nest access for ground-nesting bees and wasps (Brokaw et al 2023) and perhaps easier access to soil nutrients needed by butterflies that exhibit puddling behavior (Ankola et al 2021). A second hypothesized explanation for positive response to bare ground is that less vegetative cover creates more favorable microclimates through increased sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, we recommend broad conservation of the other pollinator taxa— A. helianthiformis , small‐dark bees, Halictus spp., and male Melissodes spp.—to help promote male fitness and pollinator diversity in these fragmented landscapes. For example, a promising recent study found that prescribed burns can increase the number of active ground‐nesting bee nest sites in prairie remnants (Brokaw et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Thinning is not the only method for creating bare ground to support ground-nesting bees; another option is prescribed fire (Sitters et al, 2016;Brokaw et al, 2023). Some plant and animal communities in North America have adaptations that enable them to thrive when exposed to periodic wildfires.…”
Section: Prescribed Firementioning
confidence: 99%